2016
DOI: 10.1071/es16010
|View full text |Cite
|
Sign up to set email alerts
|

Identifying East Coast Lows with climate hazards on the eastern seaboard

Abstract: East Coast Lows are an important weather system that can produce severe wind, wave and rainfall events along the eastern seaboard of Australia. While a number of databases of these systems have been produced, this information has historically not been readily accessible to potential users outside the research sec-tor. This paper details the development of a new product, Maps and Tables of Climate Hazards on the Eastern Seaboard (MATCHES), that bridges this gap. It combines a new database of East Coast Lows wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Further analysis into continental clusters may be advantageous, although recent studies (Cavicchia et al, 2019;Di Luca et al, 2016;Dowdy, Mills, Timbal, & Wang, 2013;Dowdy et al, 2019;Pepler et al, 2016;Pepler and Dowdy, 2021b) suggest that the frequency of these and all other cyclones are expected to decrease in the future. In contrast, Speer et al (2021) emphasise an upward trend for continental storms and, as found in this study, determined that these types of events may become more frequent in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis into continental clusters may be advantageous, although recent studies (Cavicchia et al, 2019;Di Luca et al, 2016;Dowdy, Mills, Timbal, & Wang, 2013;Dowdy et al, 2019;Pepler et al, 2016;Pepler and Dowdy, 2021b) suggest that the frequency of these and all other cyclones are expected to decrease in the future. In contrast, Speer et al (2021) emphasise an upward trend for continental storms and, as found in this study, determined that these types of events may become more frequent in the future.…”
Section: Discussionmentioning
confidence: 99%
“…By combining polygons with a dispersion statistic (variance to mean ratio) to measure the statistical significance of clusters, potentially affected regions within the study area become apparent. A modification of this method has previously been used in Australian ECL studies, whereby one geographical polygon (herein referred to as the 'ECL box'; 25 to 40 S and eastern coastline to 160 E) has been used to pre-classify tracks as ECLs before analysis (Cavicchia et al, 2019;Dowdy, Mills, Timbal, & Wang, 2013;Gray et al, 2021;Pepler et al, 2016;Speer et al, 2009Speer et al, , 2021). An alternative approach that did not rely on a defined geographical polygon was adopted by Wolff et al (2016).…”
Section: Cyclone Clustering Methodsmentioning
confidence: 99%